Tanah Negara Yang Dimasukkan Ke Dalam Boedel Pailit (Studi Kasus Putusan Pengadilan Niaga No. 04/Pdt.Sus-Pailit/2023/PN. Niaga.Mdn) - Panjaitan, Wijaya Natalia (KANJOLI Business Law Review, 2024)
The classification of assets included in the boedel bankruptcy by the curator is carried out in accordance with the provisions of laws and regulations. Problems may arise when the classification of property and assets included in the boedel bankruptcy is not an asset that should be a valid boedel bankruptcy and may be distributed to its creditors. This mistake can be fatal if the assets included in the boedel bankruptcy are assets in the form of land but it turns out that the land is state land. This study aims to analyze the legal implications of state land being included in the boedel bankruptcy. The research method used is the Normative Juridical Research Method with literature review. The legal consequences of including assets that are not the rights and property of the debtor into the boedel bankruptcy are a mistake and have an impact on the invalidity of the assets that are the object of asset management, which is also an act of illegal action because the boedel bankruptcy should only include assets that are legally owned and controlled by the bankruptcy debtor.